Development and Evaluation of a Physiologically Based Pharmacokinetic Drug-Disease Model of Propranolol for Suggesting Model Informed Dosing in Liver Cirrhosis Patients - Kalam MN; Rasool MF; Alqahtani F; Imran I; Rehman AU; Ahmed N (Dove Medical Press, 2021)
Muhammad Nasir Kalam,1 Muhammad Fawad Rasool,2 Faleh Alqahtani,3 Imran Imran,4 Asim Ur Rehman,1 Naveed Ahmed1 1Department of Pharmacy, Quaid-i-Azam University, Islamabad, 45320, Pakistan; 2Department of Pharmacy Practice, Faculty of Pharmacy, Bahauddin Zakariya University, Multan, 60800, Pakistan; 3Department of Pharmacology and Toxicology, College of Pharmacy, King Saud University, Riyadh, 11451, Saudi Arabia; 4Department of Pharmacology, Faculty of Pharmacy, Bahauddin Zakariya University, Multan, 60800, PakistanCorrespondence: Naveed AhmedDepartment of Pharmacy, Quaid-i-Azam University, Islamabad, 45320, PakistanTel +92 (51) 90644180Email natanoli@qau.edu.pkMuhammad Fawad RasoolDepartment of Pharmacy Practice, Faculty of Pharmacy, Bahauddin Zakariya University, Multan, PakistanTel +923008639046Email fawadrasool@bzu.edu.pkAim: The study was aimed to understand the underlying causes for the differences in propranolol pharmacokinetics (PK) between healthy and cirrhosis populations by using a systematic whole-body physiologically based pharmacokinetic (PBPK) model-building approach for suggesting model informed propranolol dosing in liver cirrhosis patients with different stages of disease severity.Methods: A whole-body PBPK model was developed by using population simulator PK-Sim® by using reported physicochemical and clinical data for propranolol in healthy and liver cirrhosis populations. The model evaluation was done by visual verification and comparison of PK parameters using their observed/predicted ratios (Robs/pred).Results: The developed model has effectively described the disposition of propranolol after intravenous and oral application in healthy and liver cirrhosis populations. All the model predictions were comparable to the observed clinical data and the Robs/pred for all the PK parameters were within a 2-fold range. A significant increase in plasma concentration of propranolol and decrease in drug clearance was observed in progressive stages of liver cirrhosis. The developed model after evaluation with the reported clinical PK data was used for suggesting model informed propranolol dosing in different stages of liver cirrhosis based on systemic unbound drug concentration.Conclusion: The developed PBPK model has successfully described propranolol PK in healthy and cirrhosis populations after IV and oral administration. The evaluated PBPK propranolol-cirrhosis model can have many implications in predicting propranolol dosing in liver cirrhosis patients with different stages of disease severity.Keywords: PBPK, propranolol, cirrhosis, dose adjustments, drug therapy